2008
DOI: 10.1016/j.bbi.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Glial toll-like receptor signaling in central nervous system infection and autoimmunity

Abstract: Innate immunity in the CNS depends primarily on the functions of glial cells, astrocytes and microglia, which are important for the early control of pathogen replication and direct the recruitment and activation of cells of the adaptive immune system required for pathogen clearance. Efficient immune responses are required for clearance of an invading pathogen, but dysregulation of a proinflammatory response in the CNS could lead to the development of autoimmunity. This review summarizes the activation of Toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 51 publications
9
131
0
2
Order By: Relevance
“…In vitro studies showed that heat inactivated GBS and a secreted factor 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 30 from GBS induced neuronal apoptosis via the TLR2 and MyD88 dependent production of NO from microglia. This observation is indicative of a mode of neurodegeneration that may contribute to the disease process of GBS meningitis in neonates [17]. Furthermore GBS can trigger microglial apoptosis in a pathway dependent upon TLR2 and caspase 8 [101].…”
Section: Tlrs In Response To Bacterial Meningitismentioning
confidence: 88%
See 3 more Smart Citations
“…In vitro studies showed that heat inactivated GBS and a secreted factor 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 30 from GBS induced neuronal apoptosis via the TLR2 and MyD88 dependent production of NO from microglia. This observation is indicative of a mode of neurodegeneration that may contribute to the disease process of GBS meningitis in neonates [17]. Furthermore GBS can trigger microglial apoptosis in a pathway dependent upon TLR2 and caspase 8 [101].…”
Section: Tlrs In Response To Bacterial Meningitismentioning
confidence: 88%
“…In contrast human neurons only express TLR3 [14], while Page 7 of 62 A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 both mouse and human microglia express mRNA for TLR1-9 [15] [16] (Table 1). The expression of TLR3 is particularly interesting as it is highly expressed in both murine and human astrocytes and highly expressed in the resting CNS [17] suggesting that it may have vital immune or homeostatic roles in the brain.…”
Section: Tlr Expression In Cells Of the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, IL-6 promotes Th17 and B cell differentiation [60], whereas, IFN-γ induced JAK1/2-STAT1 signaling effect which was observed in classically-activated macrophages [61] IL-27 JAK1/STAT-3 Treg IL-10, TGFRβ1 [34] JAK/STAT4 and NF-κB play important role in the pathways involved in pro-inflammatory processes [54]. Activation of the NF-κB transcription factor results in production of proinflammatory cytokines, nitric oxide (NO) and secretion of chemokines by macrophages, whereas on Dendritic cells there is increase expression of CD83, CD86, and CD40, as well as MHC class II [64] which could be important in MS pathogenesis.…”
Section: Jak/stat Pathway and Cytokines In Msmentioning
confidence: 99%